Viral infection of the kumara crop - Lewthwaite, S.L.; Fletcher, J.D. (New Zealand Plant Protection, 2010)
Viral infection within the New Zealand kumara (Ipomoea batatas) or sweetpotato crop has not been considered an important production issue until recent times The visual symptoms of viral infection may be quite inconspicuous The general presence of Sweetpotato viruses was formally acknowledged in 1989 based on published literature New Zealands first extensive kumara crop virus survey was published in 2000 Using nitrocellulose membrane ELISA this survey detected the presence of Cucumber mosaic virus (CMV) virus C6 Sweetpotato caulimolike virus (SPCaLV) Sweetpotato chlorotic fleck virus (SPCFV or C2) Sweetpotato feathery mottle virus (SPFMV) Sweetpotato latent virus (SwPLV) Sweetpotato mild mottle virus (SPMMV) and Sweetpotato mild speckling virus (SPMSV formerly C8) Sweetpotato virus G (SPVG) was first identified within New Zealand kumara in 2005 A second comprehensive crop survey using realtime reverse transcription PCR was published in 2009 This survey revealed a virus previously undetected in New Zealand Sweetpotato virus 2 (SPV2) International research and subsequent commercial experience with virustested propagation systems has shown the potential for economically significant yield and quality gains The local industry has started examining the benefits of kumara virus elimination within the New Zealand biophysical production environment